Pendampingan UMKM melalui Integrasi Storytelling Tik-Tok dan E-Wom: Strategi Penguatan Citra Merek di Era Ekonomi Digital - Nurul Afida, Febrian Nafisa; Istingadah; Rosyidah, Irma (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Although most MSME actors have adopted digital media, many of them are still unable to build a strong brand image due to limitations in d (Pratamansyah, Transformasi Digital dan Pertumbuhan UMKM: Analisis Dampak Teknologi pada Kinerja Usaha Kecil dan Menengah di Indonesia 2024)eveloping brand narratives commonly known as brand storytelling and managing Electronic Word of Mouth (E-WOM) strategically. The purpose of this study is to identify effective forms of assistance in integrating TikTok-based storytelling and E-WOM management as strategies to strengthen the brand image of MSMEs. This research employs a digital ethnography approach, which enables the researcher to observe MSME digital practices directly within online environments. Data were collected through digital content observation, in-depth interviews, and documentation of TikTok activities. The observations were conducted to examine the form and substance of video content, the narrative style employed, and audience engagement patterns such as likes, comments, and shares. The interviews aimed to explore the motivations, perceptions, and challenges faced by MSME actors in building their brand image. The findings reveal that assistance focused on developing visual narratives, understanding basic TikTok algorithms, and managing E-WOM constructively can enhance content quality, brand consistency, and audience engagement.